Retrosigmoid Craniectomy with a Layered Soft Tissue Dissection and Hydroxyapatite Reconstruction: Technical Note, Surgical Video, Regional Anatomy, and Outcomes - Magill, Stephen T.; Lee, Young M.; Rubio, Roberto R.; Nguyen, Minh P.; Heilman, Carl B.; McDermott, Michael W. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Introduction There are many reported modifications to the retrosigmoid approach including variations in skin incisions, soft tissue dissection, bone removal/replacement, and closure.Objective The aim of this study was to report the technical nuances developed by two senior skull base surgeons for retrosigmoid craniectomy with reconstruction and provide anatomic dissections, surgical video, and outcomes.Methods The regional soft tissue and bony anatomy as well as the steps for our retrosigmoid craniectomy were recorded with photographs, anatomic dissections, and video. Records from 2017 to 2019 were reviewed to determine the incidence of complications after the authors began using the described approach.Results Dissections of the relevant soft tissue, vascular, and bony structures were performed. Key surgical steps are (1) a retroauricular C-shaped skin incision, (2) developing a skin and subgaleal tissue flap of equal thickness above the fascia over the temporalis and sub-occipital muscles, (3) creation of subperiosteal soft tissue planes over the top of the mastoid and along the superior nuchal line to expose the suboccipital region, (4) closure of the craniectomy defect with in-lay titanium mesh and overlay hydroxyapatite cranioplasty, and (5) reapproximation of the soft tissue edges during closure. Complications in 40 cases were pseudomeningocele requiring shunt (n = 3, 7.5%), wound infection (n = 1, 2.5%), and aseptic meningitis (n = 1, 2.5%). There were no incisional cerebrospinal fluid leaks.Conclusion The relevant regional anatomy and a revised technique for retrosigmoid craniectomy with reconstruction have been presented with acceptable results. Readers can consider this technique when using the retrosigmoid approach for pathology in the cerebellopontine angle.
Keywords: retrosigmoid; cerebellopontine angle; anatomy; neuroanatomy; CSF leak; suboccipital; retromastoid; hydroxyapatite; reconstruction